Suplementação com própolis em rãs-touro (Rana catesbeiana) - Barbosa, Ronei Aparecido (2016)
The propolis is a biodegradable substance with effect imunostimulant, anti-inflammatory and with antioxidant properties used mainly in the form of extract. In the aquiculture there are studies developed with fishes at which the effect of the extract was valued of propolis on the zootechnic performance. However at the ranicultuae few experiments value the effect of the crude propolis, mainly at the fattening phase. The objective of this work was to evaluate the effect of different doses of propolis at the hematology and histology of Rana catesbeiana in fattening phase. A completely randomized design with four treatments: T1 = control (ration without propolis); T2 = 5 g of crude propolis/Kg ration; T3 = 15 g of crude propolis/Kg ration and T4 = 45 g of crude propolis/Kg ration.. Each treatment was valued with five repetitions (bail) with 5 animals between males and females, when 100 animals are totalizing with complete metamorphosis. The initial middle weight of the animals of 150,4 (± 23,2) grass. The animals they received commercial ration with 44 % of protein added with the different doses of crude propolis for 45 days. The analysed quantitative variables were a final weight, hematocrit, total erythrocytes and Total Plasma Protein (PPT), and the qualitative variable to presence or absence injuries in the liver and intestine. In the collection two animals of each repetition were chosen at random, rendered insensible in basin with water and ice (50 % / 50 %) and hydrochloride of benzocaine in the concentration 250mg/L. After the desensitization the animals were weighed and beheaded for collection of approximately 2 mL of blood by dropping in becker of 5 mL containing 1 drop of EDTA. All the analyses hematological were carried out up to 6 hours after the collection. The erythrocytes counting in the blood (n°/μ L) was carried out in camera of Neubauer, when 0,65 % is used physiologic solution, the determination of the hematocrit was already done by the method of - hematocrit, whereas the determination of the tenor of PPT was done when the refractometer previously calibrated with distilled water is used. For histology the liver and the intestine were fixed in formol 10 % and there followed the techniques of preparation and coloration of the blades with hematoxylin and eosin . The addition of crude propolis in the ration not interfere in the hematocrit and PPT, however, the addition of 45 g of crude propolis/Kg of ration interfered negatively in the weight of the animals and positively in the total number of erythrocytes. The use crude propolis not cause injury in the liver, small and thick intestine of the animals. This study indicates that crude propolis not cause injury and not interfere in the hematocrit and Total Plasma Protein however alters the values of weight and erythrocytes during the fattening phase